Post-Traumatic Stress Disorder, Depression, and Heart-Rate Variability among North Korean Defectors - Song, Byoung-A (Korean Neuropsychiatric Association, 2011)
OBJECTIVE: This study evaluated the symptoms of post-traumatic stress disorder (PTSD) among North Korean defectors and their level of suicidal ideation and the correlation between these and heart-rate variability (HRV) to explore the possibility of using HRV as an objective neurobiological index of signs of autonomic nervous system disorder. METHODS: A total of 32 North Korean defectors (nine men, 23 women) were selected as subjects, and their HRV was measured after they completed the Minnesota Multiphasic Personality Inventory-PTSD (MMPI-PTSD) scale and the Beck Depression Inventory (BDI). RESULTS: 1) Low-frequency (LF)/high-frequency (HF) ratios in the HRV index and MMPI-PTSD scores were correlated (r=0.419, p<0.05), as were BDI item 9 (suicidal ideation) and MMPI-PTSD scores (r=0.600, p<0.01). 2) A regression analysis of LF/HF ratios and MMPI-PTSD scores revealed an R-value of 13.8% (Adj. R(2)=0.138, F=4.695, p=0.041), and a regression analysis of BDI item 9 and MMPI-PTSD scores showed an R-value of 32.8% (Adj. R(2)=0.328, F=11.234, p=0.003). In other words, the LF/HF ratio (β=0.419) and BDI item 9 (β=0.600) appear to be risk factors in predicting MMPI-PTSD scores. CONCLUSION: The LF/HF ratio, a standard index of autonomic nervous system activity, can be used as an objective neurobiological index to analyze PTSD among North Korean defectors presenting with various mental and physical symptoms, and the approximate level of suicide -ideation can act as a predicting factor for PTSD.